+0  
 
0
136
1
avatar

Define the function $g(x)=3x+2$. If $g(x)=2f^{-1}(x)$ and $f^{-1}(x)$ is the inverse of the function $f(x)=ax+b$, find $\dfrac{a+b}{2}$.

Guest Mar 21, 2018

Best Answer 

 #1
avatar+19620 
+1

Define the function $g(x)=3x+2$. If $g(x)=2f^{-1}(x)$ and $f^{-1}(x)$ is the inverse of the function $f(x)=ax+b$, find $\dfrac{a+b}{2}$.

\(\begin{array}{|rcll|} \hline f(x) &=& ax+b \\ \hline y &=& ax+b \\\\ ax &=& y-b \\\\ x &=& \dfrac{y-b}{a} \quad & | \quad x \leftrightarrow y \\\\ y &=& \dfrac{x-b}{a} \\\\ \mathbf{f^{-1}(x)} &\mathbf{=}& \mathbf{\dfrac{x-b}{a}} \\ \hline g(x) &=& 3x+2 \\ g(x) &=& 2f^{-1}(x) \\ 3x+2 &=& 2\left( \dfrac{x-b}{a} \right) \\\\ \dfrac{3x+2}{2} &=& \dfrac{x-b}{a} \\\\ \mathbf{\dfrac{3}{2}x+1} &\mathbf{=}& \mathbf{\dfrac{1}{a}x-\dfrac{b}{a}} \quad & | \quad \text{compare} \\\\ \hline \dfrac{3}{2} &=& \dfrac{1}{a} \\ \mathbf{a} &\mathbf{=}& \mathbf{\dfrac{2}{3}} \\ \hline 1 &=& -\dfrac{b}{a} \\ \dfrac{b}{a} &=& -1 \\ b &=& -a \\ \mathbf{b} &\mathbf{=}& \mathbf{-\dfrac{2}{3}} \\ \hline \end{array} \)

 

\(\begin{array}{|rcll|} \hline \dfrac{a+b}{2} &=& \dfrac{ \dfrac{2}{3}-\dfrac{2}{3} }{2}\\\\ \mathbf{\dfrac{a+b}{2}} &\mathbf{=}& \mathbf{0} \\ \hline \end{array}\)

 

laugh

heureka  Mar 22, 2018
 #1
avatar+19620 
+1
Best Answer

Define the function $g(x)=3x+2$. If $g(x)=2f^{-1}(x)$ and $f^{-1}(x)$ is the inverse of the function $f(x)=ax+b$, find $\dfrac{a+b}{2}$.

\(\begin{array}{|rcll|} \hline f(x) &=& ax+b \\ \hline y &=& ax+b \\\\ ax &=& y-b \\\\ x &=& \dfrac{y-b}{a} \quad & | \quad x \leftrightarrow y \\\\ y &=& \dfrac{x-b}{a} \\\\ \mathbf{f^{-1}(x)} &\mathbf{=}& \mathbf{\dfrac{x-b}{a}} \\ \hline g(x) &=& 3x+2 \\ g(x) &=& 2f^{-1}(x) \\ 3x+2 &=& 2\left( \dfrac{x-b}{a} \right) \\\\ \dfrac{3x+2}{2} &=& \dfrac{x-b}{a} \\\\ \mathbf{\dfrac{3}{2}x+1} &\mathbf{=}& \mathbf{\dfrac{1}{a}x-\dfrac{b}{a}} \quad & | \quad \text{compare} \\\\ \hline \dfrac{3}{2} &=& \dfrac{1}{a} \\ \mathbf{a} &\mathbf{=}& \mathbf{\dfrac{2}{3}} \\ \hline 1 &=& -\dfrac{b}{a} \\ \dfrac{b}{a} &=& -1 \\ b &=& -a \\ \mathbf{b} &\mathbf{=}& \mathbf{-\dfrac{2}{3}} \\ \hline \end{array} \)

 

\(\begin{array}{|rcll|} \hline \dfrac{a+b}{2} &=& \dfrac{ \dfrac{2}{3}-\dfrac{2}{3} }{2}\\\\ \mathbf{\dfrac{a+b}{2}} &\mathbf{=}& \mathbf{0} \\ \hline \end{array}\)

 

laugh

heureka  Mar 22, 2018

15 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.